Cover Picture: Employing Photocatalysis for the Design and Preparation of DNA‐Encoded Libraries: A Case Study (Chem. Rec. 4/2021). Issue 4 (14th April 2021) - Kölmel, Dominik K.; Zhu, Hongyao; Flanagan, Mark E.; Sakata, Sylvie K.; Harris, Anthony R.; Wan, Jinqiao; Morgan, Barry A.
Abstract : The cover picture shows the multifaceted process, from the development of a new synthetic methodology to the subsequent selection and validation of building blocks, that led to the delivery of a photocatalytic [2+2] cycloaddition‐based DNA‐encoded library. See the Personal Account by D. K. Kölmel, H. Zhu, M. E. Flanagan, S. K. Sakata, A. R. Harris, J. Wan, and B. A. Morgan (DOI:10.1002/tcr.202000148 ).